Life-sustaining treatment preferences in older patients when referred to the emergency department for acute geriatric assessment: a descriptive study in a Dutch hospital - Daisy J. M. Ermers; Marit P. H. van Beuningen-van Wijk; Evi Peters Rit; Sonja C. Stalpers-Konijnenburg; Diana G. Taekema; Frank H. Bosch; Yvonne Engels; Patricia J. W. B. van Mierlo (BMC Geriatrics, 2021)
Abstract Background In many cases, life-sustaining treatment preferences are not timely discussed with older patients. Advance care planning (ACP) offers medical professionals an opportunity to discuss patients’ preferences. We assessed how often these preferences were known when older patients were referred to the emergency department (ED) for an acute geriatric assessment. Methods We conducted a descriptive study on patients referred to the ED for an acute geriatric assessment in a Dutch hospital. Patients were referred by general practitioners (GPs), or in the case of nursing home residents, by elderly care physicians. The referring physician was asked if preferences regarding life-sustaining treatments were known. The primary outcome was the number of patients for whom preferences were known. Secondary outcomes included which preferences, and which variables predict known preferences. Results Between 2015 and 2017, 348 patients were included in our study. At least one preference regarding life-sustaining treatments was known at referral in 45.4% (158/348) cases. In these cases, cardiopulmonary resuscitation (CPR) policy was always included. Preferences regarding invasive ventilation policy and ICU admission were known in 17% (59/348) and 10.3% (36/348) of the cases respectively. Known preferences were more frequent in cases referred by the elderly care physician than the GP (P < 0.001). Conclusions In less than half the patients, at least one preference regarding life-sustaining treatments was known at the time of referral to the ED for an acute geriatric assessment; in most cases it concerned CPR policy. We recommend optimizing ACP conversations in a non-acute setting to provide more appropriate, desired, and personalized care to older patients referred to the ED.